Nursing professional adaptation in relation to the death and dying process of patients: integrative (Research, Society and Development, 2023)
The purpose of the study was to illustrate the confrontation of nursing professionals about death, since they’re responsible for a long time care to the patient, being particularly affected with the advent of imminent death. This is a exploratory study of qualitative approach with emphasis in the experience and the confrontation of nursing professionals regarding to the process of death and dying of patients. The data were obtained the research in the following databases: Scientific Health Information from Latin America and the Caribbean Countries (LILACS) and Scientific Electronic Library Online (SCIELO). After analysing 17 articles identified that health professionals have feelings of empathy, sadness, impotence, suffering, among others. These feelings reveal the humanity of the caregiver and at the same time limit of the care often for non-involvement with the patient and their families, failing to provide humanized care, giving preference to technical and rational care. It was analyzed how many health professionals continue to feel unprepared to deal with death, being notable the need for greater reception of instructions for the nursing staff, assisting in the mental and psychological health of professionals. After all, we needed the reception of university and educational institutions, mentors, teachers, leaders of health professionals in specific nursing, to approach deepening  this theme.